Altered gut microbiome-metabolite interactions link intestinal inflammation severity and MR enterography abnormalities in Crohn’s disease - Ruonan Zhang; Zhoulei Li; Li Huang; Weimiao Kong; Yidong Zheng; Yangdi Wang; Xiaodi Shen; Lili Huang; Xinyue Wang; Qingzhu Zheng; Luyao Wu; Yaoqi Ke; et al. (iScience)
Summary: Altered gut microbiota‒metabolite interactions may result in intestinal inflammation severity variation in Crohn’s disease (CD). Magnetic resonance enterography (MRE) advances anti-inflammatory strategy development. We aimed to identify inflammation-related multiomics factors and MRE interactions for CD management, analyzing 425 CD patients and 42 healthy controls undergoing MRE, ileocolonoscopy, and fecal/blood sampling (microbiota/metabolite analyses), with intestinal inflammation categorized by MRE and ileocolonoscopy. Ruminococcus species were enriched in CD patients versus healthy controls, while Pseudomonas and Staphylococcus dominated moderate–severe versus no–mild inflammation groups, suggesting inflammation-level associations. Ruminococcus gauvreauii suppressed intestinal inflammation by regulating serum PC(O-34:3), ePE(38:6), and ceramides (all p < 0.05). Serum N-acetylneuraminic acid and guanidinoacetic acid correlated with intestinal morphological changes (e.g., MRE-detectable effusion and wall thickness) and inflammation severity (PACME < 0.05). A link was established between microscopic microbiota-metabolite markers and macroscopic imaging of inflammatory features, which could offer valuable insights into inflammation management.